Seedling growth and physiological responses of two sandplainBanksia species differing in flood tolerance - Groom, Philip (2004)
Banksia littoralis (Proteaceae) inhabits winter-wet locations and wetland fringes that are prone to seasonal flooding events on the Swan Coastal Plain. To survive in these locations, B. littoralis seedlings must be able to tolerate periods of flooding or complete submergence if establishment is to be successful. Flood tolerance was assessed in seedlings of B. littoralis subjected to 104 days of continual soil waterlogging by comparing changes in seedling growth and leaf ecophysiology with those of well-watered plants. Flood tolerance was also assessed in seedlings of Banksia prionotes, a species that grows in drier locations on the Swan Coastal Plain. As expected, B. prionotes was unable to survive long periods of soil waterlogging or submergence (97% mortality after 72 days of flooding). Both species responded to flooding by closing their stomates and reducing photosynthetic capacity, although B. littoralis was able to recover lost photosynthetic potential when flooded conditions subsided. After 72 days of flooding, there was a substantial decrease in relative growth rate in flooded B. prionotes seedlings, compared to that of well-watered plants, although this was not associated with significant differences in biomass allocation. Flood-affected B. littoralis seedlings were significantly smaller than well-watered seedlings after 72 days of flooding, but were the same size after 104 days. Flood tolerance enables B. littoralis seedlings to survive exceptionally wet winter-spring months when flooding events are more likely to occur, although surviving the annual summer drought may be more important to sustain seedling establishment.